The Usefulness of Indirect Immunofluorescence in Pemphigus and the Natural History of Patients With Initial False-Positive Results: A Retrospective Cohort Study - Kridin, Khalaf; Bergman, Reuven (Frontiers in Medicine, 2018)
The specificity and the predictive values of indirect immunofluorescence (IIF) was not estimated in real-life settings previously. The natural history of patients with false-positive results has not been elucidated sufficiently. The primary aim of the current study is to evaluate the diagnostic value of IIF analysis on monkey esophagus in pemphigus, utilizing a large cohort arising from the real-life experience of a tertiary referral center. The secondary endpoint was to determine the clinical outcomes of patients with false-positive results. This was a retrospective cohort study including all patients who were tested for the presence of intercellular autoantibodies by IIF on monkey esophagus between January 2000 and July 2017. Overall, 770 sera from different individuals were tested by IIF microscopy. Of those, 176 patients had been diagnosed with pemphigus vulgaris (PV) and 29 patients with pemphigus foliaceus (PF). The sensitivity of this immunoassay was significantly higher for the diagnosis of PV (87.4%; 95% CI, 81.5-91.9%) as compared to PF (69.0%; 95% CI, 49.2-84.7%; P=0.018). The specificity for the diagnosis of pemphigus was 93.5% (95% CI, 91.1-95.4%). Patients with false-positive results (n=37) were followed for a median duration of 5.3 years contributing 280.8 person-years. Thirty patients (81.1%) were eventually diagnosed clinically and immunopathologically with subepidermal autoimmune blistering diseases, whereas the remaining patients (18.9%) were diagnosed clinically and histologically with other inflammatory dermatoses, but none of them developed pemphigus during the follow-up duration. Of note, 7.0% (n=23) of all patients diagnosed with bullous pemphigoid (BP) in the same period (n=328) were tested positive for IgG intercellular antibodies. Histological review of the biopsy specimens of these patients did not reveal acantholysis. In conclusion, the predictive value of negative test in IIF on monkey esophagus is particularly reliable to exclude a diagnosis of pemphigus. Individuals tested positive for intercellular antibodies without an initial overt pemphigus did not show an increased risk for developing pemphigus subsequently. A sizable fraction of patients with BP showed circulating intracellular autoantibodies by IIF, without a histological evidence for acantholysis. This does not lend weight to a pathogenic role of these antibodies in patients with false-positive assays.